2022
DOI: 10.1007/s11325-021-02547-1
|View full text |Cite
|
Sign up to set email alerts
|

Positive impacts of e-aid cognitive behavioural therapy on the sleep quality and mood of nurses on site during the COVID-19 pandemic

Abstract: Objective To investigate the positive impact of e-aid cognitive behavioural therapy on the sleep quality, anxiety, and depression of nurses on site during the COVID-19 pandemic. Methods Nurses on site at the Tianjin Medical University General Hospital Airport Site experiencing insomnia, anxiety and depression during the COVID-19 prevention and control period, from February 2020 to April 2021, were selected and divided into either an e-aid cognitive behavioural therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 18 publications
(13 reference statements)
0
24
0
Order By: Relevance
“…A total of seven published RCTs 14 20 met our inclusion criteria ( Figure 1 ). Supplemental Table 4 summarizes the key characteristics of the included RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven published RCTs 14 20 met our inclusion criteria ( Figure 1 ). Supplemental Table 4 summarizes the key characteristics of the included RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies included nurses, one study included both nurses and therapists, and three included healthcare providers. The coping methods vary, including online interventional programs, 14 , 16 , 17 , 19 , 20 video-based programs, 18 and pharmacological treatment. 15 Among all coping strategies, online programs were most frequently used, including an online ambulatory intervention (expressive writing, adaptive emotion regulation activity, and positive emotion-generation activities), an online mindfulness-based stress reduction program, an e-aid cognitive behavioral therapy, and a PsyCovidApp targeting emotional skills, healthy lifestyle behavior, burnout, and social support.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two randomized controlled trials (RCTs) of cognitive behavioural therapy for insomnia (CBT‐I) demonstrated significant improvements in healthcare workers on the COVID‐19 front line. The first utilized CBT‐I delivered electronically in nurses with chronic insomnia ( n = 118) and resulted in significant improvements in sleep quality, insomnia, anxiety and depression 7 . The second was a preliminary study that administered shortened, simplified one‐shot CBT‐I to frontline healthcare providers with acute insomnia ( n = 57) achieving a significant fall in Insomnia Severity Index score from 13.3 to 6.7 8 .…”
Section: Covid‐19 and Sleepmentioning
confidence: 99%
“…The first utilized CBT-I delivered electronically in nurses with chronic insomnia (n = 118) and resulted in significant improvements in sleep quality, insomnia, anxiety and depression. 7 The second was a preliminary study that administered shortened, simplified one-shot CBT-I to frontline healthcare providers with acute insomnia (n = 57) achieving a significant fall in Insomnia Severity Index score from 13.3 to 6.7. 8 Sleep symptoms related to long COVID are reported in the international COVID sleep study (ICOSS-II) survey (n = 13,628, 16 countries).…”
Section: Covid-19 and Sleepmentioning
confidence: 99%